Classification and semiology of language disorders in children - Cuzcano Zapata, Abel (2016)
The development of language is closely linked to the general psychological evolution, so that its acquisition is immersed within the psychic world of the individual; However, language development is also linked to a progressive neuropsychological evolution, following complex processes that depend on the degree of maturation and physiology of the organism, on the one hand, and the socio-cultural environment on the other.   This complicated cognitive process, and at the same time of a modular nature, is affected by a series of language disorders that involve a large group of pathologies with extremely diverse characteristics and etiologies, which may persist in some cases, throughout life; However, its symptoms, manifestations, effects and degree of severity will depend on a complex network of factors that interact over time. Therefore it is important to highlight that in the case of children, language disorders cover a wide spectrum of symptoms that can range from slight and imperceptible difficulties for the non-specialist, to very severe and obvious problems for anyone; and from very early ages with delay only in the prelinguistic stage and in the acquisition of the first words, until an affectation of the later stages.